RELATIONSHIP BETWEEN ORGANIZATIONAL CULTURE WITH THE PARTICIPATION OF EMPLOYEES IN KOPERASI PEGAWAI TELKOM (KOPEGTEL) DYNASTY JAKARTA - Endang Sri Rahayu; Saparduddin Mukhtar; Dwi Fitri Harjanti (Jurnal Pendidikan Ekonomi Dan Bisnis (JPEB), 2013)
This study aims to determine whether there is a relationship between the Cultural Organization of the Cooperative Members Participation in Telkom Employees Cooperative (KOPEGTEL) East Jakarta. This research was conducted at Telkom Employees Cooperative (KOPEGTEL) for approximately one month, starting from November 2011 until December 2011. The method used is survey method with the correlational approach. The population in this study are all members of Koperasi Pegawai Telkom (KOPEGTEL) in East Jakarta. While the population is affordable cooperative members who are in the central office PT.Telkom East Jakarta branch. The samples used were 58 members. The sampling technique in this research is proporsial sampling technique to sample tables at the level of 5% error. Calculation of research data begins with finding regression equation and obtained y = 33.11 + 0,737X. Then test requirements normality test data analysis with error estimates using formula Lilifoers. L value obtained from the calculation count = 0.077 whereas L table for n = 58 is 0.116. Because L count <L table, then the estimated error normality test regression of Y on X indicates that the error estimates of regression of Y on X normal distribution. The results of calculations to test the significance of regression (Î± = 0.05) was obtained F count = 36.94 and F table = 4.03. Because the F count> F table, the regression model is significant. For the calculation of the regression linearity test (Î± = 0.05) was obtained F count = 0,92 and 2,08 F table. Since F arithmetic <F table, then the model is a linear regression equation. Hypothesis testing using the formula of Pearson Product Moment correlation r xy yield of 0.630 while the results of the significance test obtained t count ttable by 6.08 and 1.68. Due t count> t table, it can be concluded that there is a significant relationship between organizational culture with Cooperative Members Participation in Telkom Employees Cooperative (KOPEGTEL) East Jakarta. Calculation of the coefficient of determination showed 39.74% variation of the variable Y is determined by the variable X. It is concluded that there is a positive relationship between organizational culture relationships with the participation of Members Cooperative. More conducive organizational culture, the higher participation of the Cooperative Members